PENGARUH STRUKTUR KEPEMILIKAN, LEVERAGE, LIKUIDITAS, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2021-2023 - Mayang Puspita Dewi Saraswati; Suyatmin Waskito Adi (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to analyze the effect of ownership structure, leverage, liquidity, and profitability on firm value in manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. After the COVID-19 pandemic, the manufacturing sector faces major challenges such as inflation, global competition, and fluctuations in raw material prices that affect business continuity. The company value reflected in the stock price is an important indicator for investors in assessing the company's performance and prospects. The ownership structure, both institutional and managerial, is expected to provide control and efficiency over the management of the company. Meanwhile, leverage reflects the financial risk taken by the company, liquidity shows the ability to meet short-term obligations, and profitability reflects the ability to generate profits. This research is important to make an empirical contribution to the study of financial management as well as a reference for managers and investors in making strategic decisions in the midst of economic dynamics. The difference in results from previous research is an important basis for conducting this study.